The Blackwell Companion to Eastern Christianity. Edited by Ken Parry - Binns, John (The journal of theological studies, 2008)
This is the second volume of a projected three-part survey of the churches of Eastern Christendom. (The first part, a dictionary, was published in 1999 and the third will be a collection of primary sources.) It consists of twenty-four essays, providing accounts of the different national and regional church traditions and then of the liturgy, iconography, architecture, and hagiography of the churches. It provides a full and detailed account of the various forms of Christianity which developed in the East, and has many merits. It is exhaustive, including all the churches of the Eastern tradition, of whatever christological standpoint, and also Greek Catholic churches, and in addition the extension of these communities into the West.